Determinants of Diarrhea Self-Medication Behavior Among Urban Housewives in Bekasi, Indonesia - Salman Salman; Marisah Marisah; Uway Wariah; Iha Nursolihah (Open Access Health Scientific Journal, 2026)
Background: Self-medication is the practice of treating oneself independently. If it is done reasonably and rationally, you will get benefits, but if it is done in a bad way, there is the potential for unexpected side effects from treatment. Self-medication efforts for diarrheal diseases are often carried out by the community, considering that diarrheal diseases are included in the top 10 diseases every year in Indonesia. In 2019, Bantargebang District had the highest number of diarrhea cases, with a total of 1,610 cases. Ciketingudik sub-district had the highest number of diarrhea cases with 76 cases.Methods: This research used a quantitative cross-sectional design involving 229 homemakers with children aged 1–5 years in Ciketingudik Village, Bantargebang District, Bekasi City. The sample was selected using purposive sampling. Data were collected using a valid questionnaire to measure knowledge, attitude, environmental factors, the role of health workers, and self-medication behavior for diarrhea. Data were analyzed using univariate analysis and chi-square test with a significance level of p < 0.05.Results: The results showed that most respondents were aged 26–45 years, had a basic level of education, and were not formally employed. Statistical analysis showed that age, education, and employment were not significantly associated with self-medication for diarrhea. Conversely, knowledge, attitudes, environmental conditions, and the role of health workers were significantly associated with self-medication behavior. Respondents with good knowledge, positive attitudes, supportive environments, and active involvement of health workers were more likely to self-medicate appropriately for diarrhea.Conclusion: self-medication for diarrhea among homemakers is influenced by cognitive, behavioral, environmental, and health system factors rather than by demographic characteristics. Strengthening health education, improving environmental conditions, and enhancing the role of health workers are essential strategies for promoting safe and rational self-medication practices and reducing diarrhea-related health risks in the community.